Diverse Sphingolipid Species Harbor Different Effects on Ire1 Clustering - Bieniawski, Mark A.; Stevens, Kofi L.P.; Witham, Christopher M.; Steuart, Robert F. L.; Bankaitis, V.A.; Mousley, Carl J. (MDPI, 2022)
Endoplasmic reticulum (ER) function is dedicated to multiple essential processes in eukaryotes, including the processing of secretory proteins and the biogenesis of most membrane lipids. These roles implicate a heavy burden to the organelle, and it is thus prone to fluctuations in the homeostasis of molecules which govern these processes. The unfolded protein response (UPR) is a general ER stress response tasked with maintaining the ER for optimal function, mediated by the master activator Ire1. Ire1 is an ER transmembrane protein that initiates the UPR, forming characteristic oligomers in response to irregularities in luminal protein folding and in the membrane lipid environment. The role of lipids in regulating the UPR remains relatively obscure; however, recent research has revealed a potent role for sphingolipids in its activity. Here, we identify a major role for the oxysterol-binding protein Kes1, whose activity is of consequence to the sphingolipid profile in cells resulting in an inhibition of UPR activity. Using an mCherry-tagged derivative of Ire1, we observe that this occurs due to inhibition of Ire1 to form oligomers. Furthermore, we identify that a sphingolipid presence is required for Ire1 activity, and that specific sphingolipid profiles are of major consequence to Ire1 function. In addition, we highlight cases where Ire1 oligomerization is absent despite an active UPR, revealing a potential mechanism for UPR induction where Ire1 oligomerization is not necessary. This work provides a basis for the role of sphingolipids in controlling the UPR, where their metabolism harbors a crucial role in regulating its onset.